Effects on packaging materials on the shelf life of smoked roundscad (galunggong). - Juliano, Myra L. (College of Fisheries, University of the Philippines, 1980)
The shelf life of the traditionally smoked rounds cad and that smoked in a Mechanical Kiln was studied and compared. The samples were packed in medium density polyethylene bags, with and without vacuum, and wrapped in newspapers then stored at room temperature and at 7 degree C. Sensory and objective measurements were done. The latter include proximate analysis of the smoked product for protein, moisture, salt and ash contents and determination of peroxide and iodine values. Microbial counts and yeast and mold counts were also determined. Proximate analysis gave the following: 20.7% protein, 55% moisture, 5% salt, and 2% ash. Proximate analysis demonstrated that the type of packaging and temperature of storage stability of smoked rounds cad. Shelf lie was much improved with low temperature storage since this delayed mold growth appreciably. Packaging in polyethylene bags, with or without vacuum, enhanced microbial deterioration particularly those kept at room temperature. There were limitations encountered in vacuum packaging, tough. Wrapping in newspaper absorbed some moisture from they product and made the product drier. The type of packaging did not show significant variations in microbial counts but storage temperature had somewhat as marked effect on this. This was the same with yeast and mold count. A generally increasing peroxide value and decreasing iodine value was found inn all packed samples regardless of storage temperature. But the rates of increase and decreases were apparently faster at room temperature storage. The effect of type f packing was clearly demonstrated by the iodine numbers, the peroxide value, however, was contradictory. The shelf life of the smoked rounds cad was also affected appreciably by the type of smoke house used. Using the mechanical kiln, shelf life of the product was prolonged for more days. Appearance of the product was also much improved using this kiln as compared to the traditional smokehouse.